Identification of fish in the downstream of the Umban Sari River, Pekanbaru - Yusnita '; Deni Efizon; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The downstream of the Umban Sari River was inhabited by numerous fish species. Informationon the fish, however, is almost none. To understand the biodiversity of fish in that river, a studyhas been conducted from March to May 2016. Samplings were conducted weekly. The fish wassampled using several net types (mesh size 0.1-1.0 inch) and scoop nets. The fish sampled wereidentified based on Kottelat et al. (1993), Kottelat (2013) and Saanin (1968). Results shown thatthere were 420 fish sampled, they were belonged to 6 ordos, 10 families, 15 genus, and 17species. They were Osteochilus vittatus, Rasbora argyrotaenia, R. trilineata, Puntiusanchisporus, Parachela oxygastroides, Labiobarbus leptocheilus, Acantopsis dialuzona,Pterygoplichthys pardalis, Pangasius sp., Hemirhamphodon sp., Monopterus javanensis, Bettaimbellis, Trichopsis vittata, Trichogaster trichopterus, T. pectoralis, Pristolepis grooti andNotopterus notopterus. The fishes that present in each station were T. vittata, O. vittatus,Hemirhamphodon sp., and R. argyrotaenia (Fi 100%).Keyword: fish biodiversity, Umban Sari River, Pekanbaru, downstream